A Series of Lanthanide Metal–Organic Frameworks with Interesting Adjustable Photoluminescence Constructed by Helical Chains. Issue 29 (3rd June 2015) - Liu, Ying; Zhang, Yu; Hu, Gong Hao; Zhou, Shuai; Fan, Ruiqing; Yang, Yulin; Xu, Yan
Abstract Based on the isonicotinic acid (HIN=pyridine‐4‐carboxylic acid), seven lanthanide metal–organic frameworks (MOFs) with the formula [Ln(IN)2L] (Ln=Eu (1), Tb (2), Er (3), Dy (4), Ho (5), Gd (6), La (7), L=OCH2CH2OH) have been synthesized by mixing Ln2O3 with HIN under solvothermal conditions, and characterized by single‐crystal X‐ray diffraction, powder X‐ray diffraction, infrared spectroscopy, and fluorescence spectroscopy. Crystal structural analysis shows that compounds 1–6 are isostructural, crystallize in a chiral space group P212121, whereas compound 7 crystallizes in space group C2/c. Nevertheless, they all consist of new intertwined chains. Simultaneously, on the basis of the above‐mentioned compounds, we have realized a rational design strategy to form the doped Ln MOFs [(EuxTb1−x)(IN)2L] (x=0.35 (8), x=0.19 (9), x=0.06 (10)) by utilizing TbIII as the second "rare‐earth metal". Interestingly, the photoluminescence of [(EuxTb1−x)(IN)2L] are not only adjustable by the ratios of Eu/Tb, but also temperature or excitation wavelength.